Draft genomes of 12 host‐adapted and environmental isolates of Pseudomonas aeruginosa and their positions in the core genome phylogeny. Issue 1 (16th December 2013) - Stewart, Lewis; Ford, Amy; Sangal, Vartul; Jeukens, Julie; Boyle, Brian; Kukavica‐Ibrulj, Iréna; Caim, Shabhonam; Crossman, Lisa; Hoskisson, Paul A.; Levesque, Roger; Tucker, Nicholas P.
Abstract Pseudomonas aeruginosa is a Gram‐negative opportunistic pathogen particularly associated with the inherited disease cystic fibrosis (CF). Pseudomonas aeruginosa is well known to have a large and adaptable genome that enables it to colonise a wide range of ecological niches. Here, we have used a comparative genomics approach to identify changes that occur during infection of the CF lung. We used the mucoid phenotype as an obvious marker of host adaptation and compared these genomes to analyse SNPs, indels and islands within near‐isogenic pairs. To commence the correction of the natural bias towards clinical isolates in genomics studies and to widen our understanding of the genomic diversity of P. aeruginosa, we included four environmental isolates in our analysis. Our data suggest that genome plasticity plays an important role in chronic infection and that the strains sequenced in this study are representative of the two major phylogenetic groups as determined by core genome SNP analysis.